If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -4) = 18 Reorder the terms: -2(-4 + x) = 18 (-4 * -2 + x * -2) = 18 (8 + -2x) = 18 Solving 8 + -2x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -2x = 18 + -8 Combine like terms: 8 + -8 = 0 0 + -2x = 18 + -8 -2x = 18 + -8 Combine like terms: 18 + -8 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| -5=9+7x | | X=AW-AC^3 | | 18+(-59)+(-73)= | | 6y^2-3y=y-6 | | v-6=16 | | (1.50+2p).15=11.50 | | 7[2-(3+4x)]-2x=-9+2(1-15) | | -2(-5+4b)=-6b+8(b-5) | | -5+x=x+3 | | 2x+(35+35)=9.25 | | (3X-4)+(4X+2)= | | -9/b=5/6 | | 5(4*2-20)=4(5*2-25) | | 3k=9.87 | | 60-(-99)+28= | | 5z-7z=48 | | y=-3/4(8)+2 | | 16-5x=46 | | 5(7+4x)-7(x+7)=-79 | | (x+2)(x+2)=5+x*x | | 2/15=b/125 | | 4r+11=5-2(3-5x) | | 54+47+(-3)= | | 4-x/5=-10 | | y=-3/4(4)+2 | | (x+2)(x+2)=5+x | | 6x-x+12=32 | | -20x-8=12x+24 | | 9x+9/-9x | | 4x=3-(-5) | | (1.50+p).15=11.50 | | 2x=7-9x |